Variations in the clinical sulcus depth of healthy human gingiva: A longitudinal study - (:unkn) unknown (Blackwell Munksgaard, 1996)
Evidence is currently lacking that sulcus depths of fully erupted teeth remain unchanged in the presence of excellent oral hygiene and absence of overt gingival inflammation. In 44 healthy volunteers (age range 16-34 yr) exhibiting the above criteria, sulcus probing depths (PD) were measured with a flexible measuring strip at 6 mesio-buccal (MB) and 6 bucco-cervical (BC) sites on 6 occasions spanning a total period of 20 weeks. Analysis of the data obtained showed that PD had a total range of 0.5-4.5 mm, varying greatly between subjects, although each had a personally characteristic distribution of PD across different sites. Mean depths of MB sites and variations were greater than at BC sites. Fluctuations at BC sites may, however, be no more than measurement error whereas those at MB sites may be real, or may reflect the greater difficulty of access to MB sites than to BC ones. © Munksgaard, 1996.
Keywords: Gingival sulcus; Health; Humans; Probing